Use of organic vegetables in typical dishes of japanese cuisine - Gabriel, Camila Pires Cremasco [UNESP]; Ohara, Lika; Gabriel Filho, Luís Roberto Almeida [UNESP]; Garcia, Melina Paula Batista; Macini, Nayele; Putti, Fernando Ferrari [UNESP]; Caneppele, Fernando de Lima (Universidade Estadual Paulista - Campus de Tupa, 2015)
Recent studies have shown that organic food is safer and healthier than common food since the former is cultivated without any chemical fertilizers. Research at the Universidade Federal de Lavras, Brazil, has revealed that lettuce with organic fertilizers contains higher concentrations of phosphorus, potassium and magnesium when compared to lettuce with conventional fertilization. Research by the National Program in the Enhancement of Family Agriculture (PRONAF) has indicated higher nutritional rates in vegetables cultivated organically. Current paper is a statistical analysis on the consumption of Yakisoba (with organic products) at the trade fair in Presidente Prudente SP Brazil and identifies consumers´ knowledge on these organic products. Most yakisoba consumers are unaware of the organic products involved or believe that they are merely natural products, such as legumes, fruits and vegetables. People should be made aware of the importance of the products and their assets so that a higher demand may be established, production may be encouraged and their availability made possible at an affordable price for a larger number of people.

Em estudos realizados verificou-se que os orgânicos são mais seguros e mais saudáveis que os alimentos normais, pois são cultivados sem fertilizantes químicos ou agrotóxicos. Pesquisas na Universidade Federal de Lavras encontraram em alfaces adubadas com adubo orgânico, concentrações maiores de fósforo, potássio e magnésio, quando comparados com a alface submetida à adubação convencional. A pesquisa, realizada pelo PRONAF (Programa Nacional de Fortalecimento da Agricultura Familiar), apontou uma superioridade nutricional nas hortaliças cultivadas organicamente. O presente trabalho faz uma análise estatística do consumo de Yakissoba (com produtos orgânicos) da principal feira de Presidente Prudente e identifica o conhecimento de consumidores sobre estes produtos orgânicos. Os resultados da pesquisa demonstraram que a maioria dos consumidores de Yakissoba não tem conhecimento sobre os produtos orgânicos ou acreditam que estes produtos sejam apenas naturais, como legumes, frutas, hortaliças. Conclui-se que há necessidade de esclarecer à população sobre esses produtos e seus benefícios, para criar uma demanda, incentivar o aumento de produção, e consequentemente a disponibilidade a um preço acessível para um número maior de pessoas.
Utilização de hortaliças orgânicas em pratos típicos da culinária japonesa
Keywords: Organic products; Health; Consumption; Orgânicos; Saúde; Consumo